Treatment of a Class III growing patient with mandibular prognathism and severe anterior crossbite Tratamento de paciente Classe III em crescimento com prognatismo mandibular e severa mordida cruzada anterior - Ricardo Machado Cruz (Dental Press Editora, 2012)
The treatment of growing patients with Class III skeletal pattern represents one of the greatest clinical challenges for the orthodontist. Several treatment protocols have been proposed, almost all involving rapid maxillary expansion and maxillary protraction. However, there are cases where the maxilla is properly positioned in the anteroposterior direction and there is no transverse discrepancy, featuring only a mandibular prognathism. In such cases, when there is a set of favorable factors such as lack of laterognathism and lower mandibular plane angle, a viable option and which could prove quite interesting is the use of orthodontic chin cup during the night, aiming at trying to redirect the forward growth of the mandible. To have success, it is necessary that this procedure involves pubertal growth spurt and is extended to full skeletal maturation. This case was presented to the board of the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO) as part of the requirements to become a BBO Diplomate. O tratamento de pacientes em crescimento com padrão esquelético de Classe III representa um dos maiores desafios clínicos para o ortodontista. Vários protocolos de tratamento têm sido propostos, quase todos envolvendo expansão rápida da maxila e protração maxilar. Porém, existem casos onde a maxila está corretamente posicionada no sentido anteroposterior e não há discrepância transversa, caracterizando apenas um prognatismo mandibular. Nesses casos, quando há um conjunto de fatores favoráveis, tais como ausência de laterognatismo e menor ângulo do plano mandibular, uma opção viável e que pode se mostrar bastante interessante é o uso noturno da mentoneira, com o objetivo de tentar redirecionar o crescimento anterior da mandíbula. Para que haja sucesso, é necessário que esse procedimento envolva o surto de crescimento da puberdade e seja estendido até a completa maturação esquelética. O presente caso clínico foi apresentado à diretoria do Board Brasileiro de Ortodontia e Ortopedia Facial (BBO), como parte dos requisitos para a obtenção do titulo de Diplomado pelo BBO.